Victorian Compendium of Community-Based Resilience Building Case Studies - Critical Success Factors Help Communities Strengthen Resilience to Disasters. Issue Volume 34:Issue s1(2019) (May 2019) - Spencer, Caroline; Cross, Suzanne; McArdle, Dudley; Archer, Frank
Abstract : Introduction: Global conversations emphasize strengthening communities' resilience to disasters. These conversations inspired the Victorian Compendium of Community-Based Resilience Building Case Studies. The Compendium motivates community members to build expertise, reduce program duplication, and save valuable resources. Case study analysis identified critical success factors. Between 2012 and 2018, community groups completed an Expression of Interest to present at the MUDRI Advancing Community Resilience Forums, which provided an opportunity to impart resilience activities and knowledge. It also solved challenges and shared unforeseen learning. Over six years, 72 groups presented. Subsequently, 35 submitted their activity for consideration into the Compendium. Of these 35, 30 were included. Aim: This updated research analyses critical success factors of 30 case studies. Success factors support the key tenet of the Victorian Compendium of Community-Based Resilience Building Case Studies: to promote the sharing of achievable, practical resilience building activities. The online Compendium provides free access for all communities to explore activities before, during, and after disasters. Methods: A thematic analysis identified critical success factors of 30 Compendium case studies. Results: Case studies revealed unique and valuable learning in diverse settings. The critical success factors included: (1) strong governance, Board support, leadership and trust; (2) partnerships; (3) commitment, adaptability, and stamina; and (4) community-based initiatives. Other success factors included a paid facilitator and local government support, stamina, and celebrating success. Discussion: The Compendium represents an Australian first and offers an innovative contribution to resilience practice and research. It enhances other Victorian initiatives such as the Rockefeller funded Resilient Melbourne Strategy, which incorporates the Compendium to bring people together from across sectors to deliver distinct, yet connected actions to strengthen resilience. The Compendium enables diverse communities to adopt or adapt proven resilience activities, thereby preserving valuable resources. It offers the opportunity to extend to a national or international Compendium.